Comparação de transplantes hepáticos pediátricos submetidos à transecção hepática exsitu com ou sem a utilização da esponja de fibrinogênio e trombina humana - Vicentine, Fernando Pompeu Piza [UNIFESP] (2016)
Introduction: Pediatric liver transplantation has a low number of donor, leading for a high mortality in the awaiting list. A strategy for increase the number of liver transplantation is the utilization of ex-situ liver transection (reduction or split), but this technique is not free of complications such as hemorrhage of the wound area and bile leak. The fibrinogen and thrombin human sponge, is a tool for the hemostasis in the liver surgery. The use of fibrinogen and thrombin human sponge is described in the literature for hemostasis in liver resection, and new papers reported its use in the liver transplantation field. Aims: Compare the pediatric liver transplantation with the ex-situ liver transection (reduction or split) with or without the utilization of fibrinogen and thrombin human sponge. Methods: Were analyzed prospectively 21 patients underwent liver transplantation with ex-situ liver transection (reduction or split) with the utilization of fibrinogen and thrombin human sponge in the wound area (group A), and retrospectively 59 patients underwent liver transplantation with ex-situ liver transection (reduction or split) without the sponge (group B). Results: Recipient and donor characteristics were similar in both group. In the group A 85,7% patients underwent to split liver transection and in group B 61% (p = 0,056). When we compare the number of reoperations we did not found difference in both group, but we observed a lower number of reoperation caused by hemorrhage of the wound area in the group A (14,2%) comparing to the group B (41,7%), p = 0,029. Regarding bile leak in the wound area there was no difference in both group (A: 17,6%, B: 5,1%, p = 0,14). Conclusion: Comparing both groups, in this population, there was a small number of reoperations by hemorrhage of wound area in pediatric patients underwent liver transplantation with ex-situ liver transection (reduction or split) with the fibrinogen and thrombin human sponge.